PHARMACOLOGICAL EVALUATION OF CENTRAL ANALGESIC ACTIVITY OF ACACIA CATECHU BY HOT PLATE AND TAIL IMMERSION METHOD - AHIRWAR, VIMLA; SAHU, MANOJ KUMAR; VERMA, LOKESH; BANWEER, JITENDRA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The aim of the study was to evaluate the analgesic activity of Acacia catechu heartwood extracts on Swiss albino mice using hot plate and tail immersion method. Methods: In this study, we used the aqueous and methanol extracts of heartwood of A. catechu to evaluate its analgesic activity. The aqueous extract was achieved by doubled distillation method and the methanol extract was achieved by cold maceration method. The mice were divided into four groups, each group consisting of six animals. Doses of 50, 100, and 300 mg/kg, p.o. of both the extracts of A. catechu were given to the mice. The responses were noted at 0, 15, 30, and 60 min. Results: The results of both the methods were quick similar but differ based on extracts. The aqueous extract of A. catechu showed a much better yield of analgesic activity as compared to the methanol extract. The data were analyzed by graph using two-way analysis of variance, which showed the dose-dependent pain resistance. Conclusion: The study confirmed the potency of A. catechu in pain management and points the future development to be conducted on it.